تحسين أداء نظم المراقبة باستخدام ميزات أساسية للصور الفيديوية (اللون والحواف والبنية) - حجازية محمد; اسماعيل أسامة (Latakia University Journal -Engineering Sciences Series, 2017)
يقترح البحث آلية جديدة تهدف إلى زيادة فاعلية نظم المراقبة عن طريق تحديد الأشياء المتحركة الحاصلة أمام كاميرة مراقبة والتعرف عليها واقتراح آلية جديدة لفهرستها وتخزينها ضمن قاعدة بيانات و تصنيفها وفق الخصائص الأساسية لها والمؤشرات القوية الموجودة فيها واسترجاعها عند الحاجة إليها بأقل زمن ممكن. الفكرة الأساسية تكمن في الدمج بين الخصائص الأساسية للهدف وهي اللون والحواف والبنية والذي يضمن أفضل أداء في استخلاص الميزات الأساسية للهدف, ومن ثم إجراء التحويلات اللاخطية على حواف الهدف بهدف الحصول على صورة تحمل أدق التفاصيل والاعتماد عليها كفهارس, بعد ذلك يتم إجراء التحويلات المعاكسة على حواف الهدف أثناء عملية استرجاعه من قاعدة البيانات. أخيراً تم اقتراح آلية فهرسة جديدة تضمن استرجاع الأهداف المطلوبة بأفضل دقة وأقل زمن و تم تصميم البرنامج اللازم لتحقيق ذلك. This Research suggests a new mechanism that aims to increase the effectiveness of surveillance systems by extracting the moving objects coming from surveillance camera in order to identify them and propose a new mechanism for indexing and storing in database and classified them according to the basic characteristics and strong indicators and retrieval when needed in less possible time. The basic idea lies in the combination of the basic characteristics of the goal (color, edges and texture) which ensures the best performance in extracting the basic target features and depend on it as indexes, then nonlinear transfers has been done on the edges of the target in order to get a picture bearing the minutest details, then conducted adverse transfers on the edges of the target during the process retrieved from the database. Finally, we propose a new mechanism for indexing all images tabase to Retrieval them in best accuracy and less time, and a program had been achieved to realize this idea.